2023
DOI: 10.1007/s12015-023-10591-5
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin-pretreated Human cardiac-specific c-kit+ Cells Enhance Exosomal miR-3059-5p and Promote Angiogenesis Against Hindlimb Ischemia in mice

Abstract: Aims: Protection of cardiac function following myocardial infarction was largely enhanced by bradykininpretreated cardiac-speci c c-kit + (BK-c-kit + ) cells, even without signi cant engraftment, indicating that paracrine actions of BK-c-kit + cells play a pivotal role in angiogenesis. Nevertheless, the active components of the paracrine actions of BK-c-kit + cells and the underlying mechanisms remain unknown.This study aimed to de ne the active components of exosomes from BK-c-kit + cells and elucidate their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…After treatment, the migration ability of the HUVECs was tested by using the Transwell assay as previously reported. 22 , 23 , 24 , 25 Briefly, a total of 2 × 10 4 HUVECs (passage 3–8) were suspended in 200 μL ECM medium (0% FBS) and seeded in a modified Boyden chamber with an 8 μm‐pore polycarbonate membrane (Corning, USA) for 30 min. The lower chambers were placed with 600 μL ECM medium (2.5% FBS).…”
Section: Methodsmentioning
confidence: 99%
“…After treatment, the migration ability of the HUVECs was tested by using the Transwell assay as previously reported. 22 , 23 , 24 , 25 Briefly, a total of 2 × 10 4 HUVECs (passage 3–8) were suspended in 200 μL ECM medium (0% FBS) and seeded in a modified Boyden chamber with an 8 μm‐pore polycarbonate membrane (Corning, USA) for 30 min. The lower chambers were placed with 600 μL ECM medium (2.5% FBS).…”
Section: Methodsmentioning
confidence: 99%
“…Unilateral HLI was induced, as previously reported. 28 Briefly, mice were anesthetised by isoflurane vaporisation. The entire femoral artery was exposed and ligated using nylon thread.…”
Section: Methodsmentioning
confidence: 99%
“…The -Kit signaling pathway has been extensively studied in the cancer field, and its angiogenic properties are well characterized [ 19 , 20 ]. Moreover, a few studies, including one from our group [ 21 ], have shown the beneficial effect of global c-Kit in improving arteriogenesis and limb perfusion during hindlimb ischemia [ 22 , 23 ]. However, the specific effect of vascular c-Kit signaling is poorly understood.…”
Section: Introductionmentioning
confidence: 99%